Effectiveness evaluation of discrete macromodelling to forecast power consumption of electric power system component elements - Stakhiv, Petro; Kozak, Yuriy; Hoholyuk, Oksana (Publishing House of Lviv Polytechnic National University, 2016)
The paper is concerned with a method intended for forecasting electric power consumption using discrete macromodels of daily and annual electric power consumption of defined objects. The method provides the possibility of estimating qualitative characteristics of future electric power consumption based on known prior data. The procedure of development of a mathematical macromodel for the electric power consumption forecasting by using the evolution algorithms is described; it is based on the discrete autonomous macromodels in the form of state equations using “black box” approach. A discrete autonomous macromodel of annual power consumption of a real component element has been developed as a test example for the proposed technique. Effectiveness of the discrete equation apparatus application for power consumption forecasting of electric utilities has been evaluated. Запропоновано метод прогнозування добового та річного споживання електроенергії визначених об’єктів з використанням дискретних макромоделей, який дає змогу оцінювати динаміку споживання електричної енергії у майбутньому на основі відомих попередніх даних. Описано процедуру побудови моделі на основі дискретних автономних макромоделей у вигляді “чорної скриньки” для прогнозування енергоспоживання з використанням еволюційного підходу для конкретних об’єктів. Побудовано дискретну автономну макромодель річного енергоспоживання реального об’єкту за один рік як перевірку запропонованого підходу. Оцінено ефективність використання апарату дискретних рівнянь стану для прогнозування енергоспоживання об’єктів енергетики.
Застосування дискретних макромоделей для прогнозування енергоспоживання об’єктів електроенергетичних систем
Keywords: electric power system; macromodel; forecasting; power consumption; optimization